The Girl on the Train - Hawkins, Paula (New York : Riverhead Books, a member of Penguin Group (USA), 2015)
Rachel takes the same commuter train every morning, flashing past a stretch of cozy suburban homes, and stopping at the signal that allows her to daily watch the same couple breakfasting on their deck. Their life, as she sees it, is perfect ... until she sees something shocking. Its only a minute until the train moves on, but now everything is changed. Rachel goes to the police, and becomes inextricably entwined in the lives of everyone involved. Has she done more harm than good?
Keywords: Railroad travel -- Fiction; Commuters -- Fiction; Strangers -- Fiction; London (England) -- Fiction; Fiction; Psychological fiction; Thrillers (Fiction); Suspense fiction; Psychological fiction; Thrillers (Fiction); Suspense fiction